2010
DOI: 10.1097/tp.0b013e3181f24e8d
|View full text |Cite
|
Sign up to set email alerts
|

Validation of Recently Proposed Consensus Criteria for Thrombotic Microangiopathy After Allogeneic Hematopoietic Stem-Cell Transplantation

Abstract: Both proposed consensus criteria have major pitfalls in their use as uniformly accepted diagnostic criteria for TMA. The use of O-TMA as a broad definition for TMA and the grading system by the presence of renal involvement may be a counterproposal for future trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
235
0
6

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 249 publications
(260 citation statements)
references
References 21 publications
7
235
0
6
Order By: Relevance
“…1 The reported incidence of TA-TMA varies greatly from 0.5-63.6%, which is at least partly a consequence of the marked discrepancy in the definitions used and the lack of uniform criteria for diagnosis. 2 A generalized endothelial dysfunction, independent of ADAMTS-13 activity, appears to be the key event that represents the final common pathway of the disease, resulting in thrombosis and fibrin deposition in the microcirculation.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 The reported incidence of TA-TMA varies greatly from 0.5-63.6%, which is at least partly a consequence of the marked discrepancy in the definitions used and the lack of uniform criteria for diagnosis. 2 A generalized endothelial dysfunction, independent of ADAMTS-13 activity, appears to be the key event that represents the final common pathway of the disease, resulting in thrombosis and fibrin deposition in the microcirculation.…”
Section: Introductionmentioning
confidence: 99%
“…2 The exact pathophysiology of TA-TMA remains unclear, but a variety of potential risk factors have been suggested. 1,3,5,8,[10][11][12][13][14] The use of TAC plus SIR as GVHD prophylaxis has been associated with an increased incidence of TA-TMA, which ranges from 10.8-55%, the latter in patients who received BU plus CY as part of their conditioning regimen. [17][18][19]21,22 In a recent phase II multicenter prospective trial conducted by our group, including some of the patients in this study, no differences were observed in the incidence of TA-TMA when TAC/SIR was compared with patients included in a prior prospective trial using CYA-mycophenolate (the overall incidences of TA-TMA were 10% and 6%, respectively).…”
Section: Baseline Characteristics Of Patientsmentioning
confidence: 99%
See 1 more Smart Citation
“…According to recent literature data [1,9] Due to non-availability of Defibrotide, a drug possibly effective in the treatment of TAM [10] and keeping in mind CMV reactivation and/or CSA as suspected causes of TAM we had no management option other than optimizing CMV treatment, decreasing CSA dose and introducing Mycophenolate mofetil for GVHD prophylaxis. These measures resulted in favourable outcome most probably because there was no associated GVHD.…”
Section: Discussionmentioning
confidence: 99%
“…Varying levels of awareness among institutions, diagnostic doubt and limited prospective data are reflected in the wide range of reported incidences of TA-TMA (from 0.5 to 76%). 64 TA-TMA is a member of the family of thrombotic microangiopathies, including, among others, thrombotic thrombocytopenic purpura and hemolytic uremic syndrome. 65 TA-TMA ensues when endothelial damage in the setting of HCT results in microangiopathic hemolytic anemia and platelet consumption, culminating in thrombosis and fibrin deposition in the microcirculation.…”
Section: Pathogenesismentioning
confidence: 99%